The Sea of Trolls - Farmer, Nancy, 1941- (New York : Atheneum Books for Young Readers, 2004)
After Jack becomes apprenticed to a Druid bard, he and his little sister Lucy are captured by Viking Berserkers and taken to the home of King Ivar the Boneless and his half-troll queen, leading Jack to undertake a vital quest to Jotunheim, home of the trolls.
Includes bibliographical references (page [457]-459).
Parents' Choice, January 2004.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal starred, October 2004.
Notable/Best Books (A.L.A.), January 2005.
Keywords: Mythology, Norse -- Fiction; Druids and druidism -- Fiction; Vikings -- Fiction; Bards and bardism -- Fiction; Saxons -- Fiction; Brothers and sisters -- Fiction; Trolls -- Fiction; Norse mythology -- Fiction; Siblings -- Fiction